A Vibrational Spectroscopic Study of the Adsorption of 4 4 Bipyridiyl by Smectite Group Clay Minerals From Anatolia Turkey - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Kluwer Academic Publishers, 1993)
The adsorption of 4,4′-bipyridyl by natural sepiolite and smectite group clay minerals (bentonite, hectorite and saponite) from Anatolia (Turkey) has been studied using vibrational spectroscopy. Investigation of Fourier-transform infrared and Fourier-transform Raman spectra of adsorbed 4,4′-bipyridyl indicate the presence of chemisorbed species. However, any evidence for the generation of anionic species on the surface of the phyllosilicates has not been detected. It is proposed that the adsorbed bipyridyl molecules on sepiolite are centrosymmetric and H-bonded to the surface hydroxyls through both the nitrogen lone pairs as bidentate ligands. The adsorbed bipyridyl molecules on the smectite group clays are coordinated to exchangeable cations both directly and also indirectly through water as monodentate ligands. XRD patterns of the clays studied are also recorded.
Keywords: FT-IR spectroscopy; FT-Raman spectroscopy; clays; sepiolite; bentonite; hectorite; saponite; 4,4′-bipyridyl; adsorption; XRD